Evaluation of infestation in parasitoids on Metisa plana Walker (Lepidoptera: Psychidae) in three oil palm plantations in Peninsular Malaysia - Halim M.,; Muhaimin A. M. D.,; Syarifah Zulaikha S. A.,; Nor Atikah A. R.,; Masri M. M. M.,; Yaakop S., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
The bagworm, Metisa plana Walker (Lepidoptera: Psychidae) is one of the most dominant pest species on oil palm plantations in Malaysia which can cause high yield loses up to 43% over two years after a serious infestation. Parasitoids play an important role as natural enemies to reduce bagworm’s population. The interaction of this pest and parasitoids are highly influenced by the availability of bagworms as a host. Highly infested oil palm plantation in Banting, Selangor, Tapah, Perak and Yong Peng, Johor were chosen as sampling sites. This study represented parasitoids species that associated with Metisa plana namely Cotesia metesae (51%: 70 individuals), Brachymeria carinata (21%: 28 individuals), Buysmania oxymora (13%: 18 individuals), Goryphus bunoh (8%: 11 individuals), Pediobius sp. (5%: 7 individuals) and Eupelmus cotoxanthae (2%: 3 individuals) in highly infested oil palm plantation in Peninsular Malaysia. It is known that parasitoid species Cotesia metesae recorded the highest number of emergence among all parasitoids and presence in all sampling sites. The information regarding parasitoids species in oil palm plantation is crucial in order to regulate the bagworms population.